Cyclosporin A Prevents Ovarian Graft Rejection, and Permits Normal Germ Cell Maturation Within the First 5 Weeks Post-transplantation, in the Domestic Turkey (Meleagris gallopavo) - Hall, George B.; Beeler-Marfisi, Janet; Long, Julie A.; Wood, Benjamin J.; Bedecarrats, Gregoy Y. (Frontiers in Veterinary Science, 2022)
Biobanked ovaries collected from recently hatched poults can only be revived through transplantation, using a recipient bird. The main hurdle in transplantation is preventing graft rejection, which appears as lymphocytic infiltration upon histologic evaluation of the graft. In this study, the condition of the transplants (immunological compatibility (auto- vs. allotransplants), donor age, time in holding media, and temperature of holding media) and treatment of recipient poults with varying immunosuppressants (mycophenolate mofetil (MFM), cyclophosphamide (CY), and cyclosporin A (CsA)) were studied to determine which factors could reduce lymphocytic infiltration, during the first 35 days post-transplantation. Lymphocytic infiltration was determined via cytoplasmic CD3 (T cell) and nuclear PAX5 (B cell) expression. There was no significant difference in the percent of cytoplasmic CD3 or nuclear PAX5 immunostained area between the unoperated group and the autotransplants, by 6 days post-transplantation. However, the allotransplants had more (P < 0.05) positive cytoplasmic and nuclear immunostained areas compared to autotransplants, irrespective of donor age, time in holding media or temperature of the media. By 14 days post-transplantation, the CsA 25 and 50 mg/kg/day treatment groups had less (P < 0.05) CD3 and PAX5 positive areas in their allotransplants, compared to the unsuppressed group. At 35 days post-transplantation, the CsA 25 mg/kg/day allotransplant group also had less (P < 0.05) CD3 and PAX5 positive areas compared to the unsuppressed group. The CsA 25 mg/kg/day transplants also had a similar ovarian follicular size compared to the unoperated group, although they contained fewer (P < 0.05) follicles based on follicular density. Donor age, duration in holding media, temperature of media, and treatment of recipients with MFM or CY had no effect on reducing lymphocytic infiltration. However, immunological compatibility was associated with decreased lymphocytic infiltration, as autotransplants had little lymphocytic infiltration. Treatment of recipients with CsA at 25 mg/kg/day was also associated with reduced lymphocytic infiltration and allowed transplants to develop normally during the first 35 days post transplantation.